PERAN GURU SOSIOLOGI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X - Remigius, Remigius; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The generalÂ  problem in this research is how the role of sociology teacher in increasing the learning motivation of students in class X sman 1 nanga taman. In this research the method used is descriptive method with qualitative research form. Data collection techniques used are direct observation techniques, direct communication techniques and documentary study techniques, while the data collection tools used are observation, interviews, and documentation. From the results of the study it can be concluded that the sociology teacher in increasing student motivation in class X is good, seen from the efforts of teacher who actively approach the students and continue to try to provide guidance and training in learning activities, so students are more motivated to take part in learning and understand what is being conveyed.In addition the teacher also provides input to students whose achievements are still lacking, and provide assistance to students who need to be given additional intensive lessons. Thus then, the role of teacher in increasing student learning motivation is very influential in determining the success of education in schoolÂ Keyword: The Role of Sociology Teacher, Student motivation.